"Perrotta Individual Sexual Matrix Questionnaire" (PSM-Q): Technical updates and clinical research - Giulio Perrotta (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Purpose: With regard to studies on sexual behaviors, this research proposes a series of updates to the previous edition in order to improve its administration; at the same time, a sample of the population is administered to test its reliability, usefulness and psychometric consistency.  Methods: Clinical interview with administration of the "Perrotta Individual Sexual Matrix Questionnaire" (PSM-Q), updated.  Results: Once the questionnaire was completed, it was tested on a population sample of 600 subjects, so distributed: the clinical group composed of 300 subjects, of which 150 male and 150 female, and the control group composed of 300 subjects, of which 150 male and 150 female. In particular: in the "control group", no psychopathological disorder was detected, and the sexual behaviors detected did not meet the requirements of paraphiliac disorder; in the "clinical group", on the other hand, 70% (210/300, 118 men and 92 women) confirmed their psychopathological condition, identifying, thanks to the questionnaires administered, a better framing of their state of health, facilitating the psychotherapeutic approach and the remaining 30% (90/300, 32 men and 58 women), on the other hand, repositioned their sexual dimension by virtue of a different framing, including a psychopathological one, confirming the usefulness of the questionnaires administered precisely in a psychodiagnostic key. Conclusions: The present research improves on previously published work (Perrotta Individual Sexual Matrix Questionnaire", PSM-1) and frames it in the conscious and functional use of patients who manifest symptomatology of a sexual nature or with sexual involvement. In fact, the use of the questionnaires provided is functional to frame in a more detailed and methodological way the sexual universe of the patient, through the compilation of sections B, C and D (first part), while the compilation of sections D (second part) and E helps the therapist to designate in a direct and clear way about the habitual sexual behavior and the relational style of the couple; finally, it will be the duty of the therapist to apply the diagnostic criteria of the DSM-V in order to identify the presence or absence of any paraphilias that have in themselves the characteristics of a paraphiliac disorder properly determined.